1993
DOI: 10.1056/nejm199311113292001
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Management without Antibiotics of Fever in Selected Infants

Abstract: With the use of strict screening criteria, a substantial number of febrile one-to-two-month-old infants can be cared for safely as outpatients and without antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
350
1
11

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 426 publications
(371 citation statements)
references
References 12 publications
9
350
1
11
Order By: Relevance
“…Several management protocols have been published. 9,10,15,[17][18][19] Some studies have shown that selected febrile infants may safely be managed as outpatients without the use of antibiotics. 10,18,19 Those infants had to meet more stringent risk criteria than ours to qualify for outpatient management, and 75% of the most recent study population of infants 29 to 60 days old using this strategy were admitted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several management protocols have been published. 9,10,15,[17][18][19] Some studies have shown that selected febrile infants may safely be managed as outpatients without the use of antibiotics. 10,18,19 Those infants had to meet more stringent risk criteria than ours to qualify for outpatient management, and 75% of the most recent study population of infants 29 to 60 days old using this strategy were admitted.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,15,[17][18][19] Some studies have shown that selected febrile infants may safely be managed as outpatients without the use of antibiotics. 10,18,19 Those infants had to meet more stringent risk criteria than ours to qualify for outpatient management, and 75% of the most recent study population of infants 29 to 60 days old using this strategy were admitted. 19 In our population, the strategy of Baskin et al 15 was used, so all children were treated with antibiotics but only 39% (42% of 28-to 60-day-old infants and 34% of 61-to 90-day-old infants) were admitted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, most studies on evaluation and treatment of febrile young infants place neonates in a separate category. [1][2][3][4][5] Widely followed guidelines recommend a complete evaluation of febrile neonates, even if well appearing, for SIs and admission to the hospital for presumptive antibiotics. 6 A few authors have attempted to define low-risk criteria for treating these patients less conservatively.…”
mentioning
confidence: 99%
“…Recently, a comprehensive review of the literature (9) suggested that children 29 to 90 days old at low risk can also be investigated without a lumbar puncture and be discharged with no empirical treatment and follow-up based on the results of the blood and urine tests in the emergency department (ED). It is important to note that children in the Philadelphia study did not receive antibiotics if they were considered to be at low risk (8). Also note that in their study, low-risk criteria mandated a lumbar puncture.…”
Section: Management Of 29-to 90-day-old Infantsmentioning
confidence: 98%